Functional impairment of the kidneys with their acute damage in patients with peritonitis - Saensus, M.; Gozhenko, A. (Journal of Education, Health and Sport, 2025)
The aim of our study was to study renal function and processes in patients with peritonitis. The results of a study of 32 patients with peritonitis compared with 11 healthy individuals showed that patients showed signs of acute kidney injury (AKI), judging by the presence of urinary syndrome. Two periods of APF have been identified: preazotemic and azotemic with the development of acute renal failure, in which the glomerular filtration rate decreases. Proteinuria and sodium excretion have been shown to increase, but not definitively. Whereas when converted to a unit of glomerular filtration rate, they increase significantly. The proposition about the primary tubular-tubular compensation mechanism, which turns into the tubular-glomerular one, which reduces glomerular filtration and prevents sodium loss, is substantiated.